Depletion of the transcriptional coactivators megakaryoblastic leukaemia 1 and 2 abolishes hepatocellular carcinoma xenograft growth by inducing oncogene-induced senescence - Hampl, Veronika; Singer, Stephan (EMBO molecular medicine, 2013)
Megakaryoblastic leukaemia 1 and 2 (MKL1/2) are coactivators of the transcription factor serum response factor (SRF). Here, we provide evidence that depletion of MKL1 and 2 abolishes hepatocellular carcinoma (HCC) xenograft growth. Loss of the tumour suppressor deleted in liver cancer 1 (DLC1) and the subsequent activation of RhoA were prerequisites for MKL1/2 knockdown-mediated growth arrest. We identified oncogene-induced senescence as the molecular mechanism underlying the anti-proliferative effect of MKL1/2 knockdown. MKL1/2 depletion resulted in Ras activation, elevated p16 expression and hypophosphorylation of the retinoblastoma (Rb) protein in DLC1-deficient HCC cells. Interestingly, reconstitution of HuH7 HCC cells with DLC1 also induced senescence. Evaluation of the therapeutic efficacy of MKL1/2 knockdown in vivo revealed that systemic treatment of nude mice bearing HuH7 tumour xenografts with MKL1/2 siRNAs complexed with polyethylenimine (PEI) completely abolished tumour growth. The regression of the xenografts was associated with senescence. Importantly, PEI-complexed MKL1 siRNA alone was sufficient for complete abrogation of HCC xenograft growth. Thus, MKL1/2 represent promising novel therapeutic targets for the treatment of HCCs characterized by DLC1 loss.
Gesehen am 08.10.2021